PEDAGOGICAL SKILLS OF THE TEACHER IN THE FORMATION OF DESIGN SKILLS IN STUDENTS - To‘xtayeva Zebo Sharifovna; Asrorova Saodat Abdullo qizi (American Journals, 2024)
This article discusses the teacher's skills and his role in the formation of students' project creation skills, noting that pedagogical skills, personal characteristics, work experience and pedagogical techniques are important in this process as an important factor ensuring the success of the teacher's professional activity, taking into account the interests and needs of the teacher students to improve the effectiveness of the educational process. The ways of applying a creative approach, the object of pedagogical activity within each topic is a person and the correct organization of the teacher's role, as well as pedagogical abilities and techniques are analyzed.
Keywords: Pedagogical skills, project creation, skills, teacher, educational process, pedagogical activity, creative approach, pedagogical abilities, students, innovative activities